Central Hyperthermia Treated with Bromocriptine. (28th February 2017) - Natteru, P.; George, P.; Bell, R.; Nattanmai, P.; Newey, C. R.
Abstract : Introduction . Central hyperthermia is common in patients with brain injury. It typically has a rapid onset with high temperatures and marked fluctuations and responds poorly to antibiotics and antipyretics. It is also associated with worse outcomes in the brain injured patient. Recognizing this, it is important to aggressively manage it. Case Report . We report a 34-year-old male with a right thalamic hemorrhage extending to the midbrain and into the ventricles. During his admission, he developed intractable fevers with core temperatures as high as 39.3°C. Infectious workup was unremarkable. The fever persisted despite empiric antibiotics, antipyretics, and cooling wraps. Bromocriptine was started resulting in control of the central hyperthermia. The fever spikes were reduced to minor fluctuations that significantly worsened with any attempt to wean off the bromocriptine. Conclusion . Diagnosing and managing central hyperthermia can be challenging. The use of bromocriptine can be beneficial as we have reported.